Research in popular education and Basic Education (Práxis Educativa, 2013)
This paper analyses the relation between popular education and Basic Education, focusing mainly on the impact of popular education research on policies and practices of basic education. Initially, a reflection is proposed about popular education as a field of research in which, from investigation and education practices, a methodological proposal with singular characteristics is developed. The second theme for reflection is the reconstitution of the relation between popular education and basic education as two fields of pedagogical practices which vary from formal, non-formal and informal. The parameters of analysis are works presented in the ANPEd (Post-Graduation and Educational Research National Association) meeting. Results point to some emerging tasks for the popular education research and their implications to basic education. Keywords: Popular education. Basic Education. Participatory research.